(untitled) (Bioscience Journal, 2018)
The level of knowledge and training of nursing staff has been related to indicators of quality of care in health, although the application of indicators is still rare related to continuing education programs. The aim of this study was to use the training indicator to evaluate the efficiency of a Continuing Education Program focused on nursing staff in a Brazilian university hospital. In addition, it also checked if different nursing staff characteristics interfere in the training indicator. The number of hours that each nursing professional spent in the program was measured, and this indicator was related to professional features like professional category, unit of work, employment link and department. We note that inpatient sectors and high-complexity care feature a greater average number of hours when compared to units of lower complexity or support or administrative sectors. Another relevant point was the lower number of hours of training of nurses compared to other nursing categories, highlighting the need to consider different strategies for each nursing category. Despite this, nurses that perform assistance compared to those who perform only administrative activities showed no differences in participation. We observe that the profile of professionals was a relevant factor in participating in the program, and that this must be taken into consideration in the planning of continuing education programs. The program in this institution, which has compulsory participation during working hours, was also effective compared to the few studies that have measured the number of hours of training in hospitals of high complexity.